Kefiran cryogels as potential scaffolds for drug delivery and tissue engineering applications - Radhouani, Hajer (2019)
A Kefiran-based scaffold was developed using a freeze gelation technique, and its potential use for both drug delivery system and tissue engineering applications were investigated. This scaffold showed, through micro-computed tomography and scanning electron microscopy, high porosity (82.3 ± 4.4%), thick pore walls (13.4 ± 0.7 μm), aerogel form with foam-like structure, and elastic behaviour (δ = 16 ± 0.7°). Moreover, the Kefiran scaffold degradation showed a delayed profile for over 28 days. The developed scaffold allowed a slow and sustained diclofenac release over two weeks, and the human Adipose-derived Stem Cells, cultured onto the Kefiran scaffold, were metabolically active after 72 h. Therefore, our research suggests that Kefiran cryogel could be a potential candidate for drug delivery of controlled bioactive molecules and tissue engineering scaffolding.